Factors associated with health-related quality of life in patients undergoing percutaneous coronary intervention: Thai PCI registry - Siriyotha, Sukanya; Pattanaprateep, Oraluck; Srimahachota, Suphot; Sansanayudh, Nakarin; Thakkinstian, Ammarin; Limpijankit, Thosaphol (Frontiers in Cardiovascular Medicine, 2023)
Background: Percutaneous coronary intervention (PCI) has been shown to improve health-related quality of life (HRQoL) in patients with coronary artery disease (CAD). The objectives of this study were to assess the changes in HRQoL and factors influencing these changes in CAD patients after undergoing PCI. Methods: Data from a nationwide PCI registry across 39 hospitals in Thailand were collected in 2018-2019, including baseline characteristics, comorbid diseases, angiographic CAD severity, procedural details, and type of health insurance. HRQoL, as measured by utility scores, was determined in all patients using the Thai version of EQ-5D-5L at admission, discharge, and 6 and 12 months after discharge. The effects of time after PCI procedure and various factors on mean utility scores were assessed using a mixed-effect linear regression model. Results: A total of 19,701 patients were included in the analysis; they had a mean age of 64.2 ± 11.7 years and were predominantly (69.1%) male. Following PCI, the mean utility scores increased from 66.6 ± 19.6 at admission to 81.9 ± 13.8 at discharge, and remained stable at 6 and 12 months (86.1 ± 12.3 and 88.0 ± 11.7, respectively). After adjusting for potential confounding variables, several factors were found to be independently associated with improved HRQoL, including angiographic success, male gender, overweight status, dyslipidemia, and radial access. Six other factors were associated with less improved HRQoLs, including cardiogenic shock/IABP support, old age, CKD, clinical presentation (STEMI and NSTEMI), prior cerebrovascular disease, and heart failure. There were no associations of CAD severity and procedural details with HRQoL. No differences were found related to type of health insurance, except that patients who were uninsured or self-pay tended to have less improvement in HRQoL. Conclusion: HRQoL improved significantly after PCI in these subjects, as observed through one year of follow-up. Identifying the factors influencing these improvements may assist clinicians in tailoring patient interventions to optimise quality of life after PCI.